Dynamics and Evolution of Galactic Nuclei. - Merritt, David (Princeton series in astrophysics., 2013)
Deep within galaxies like the Milky Way, astronomers have found a fascinating legacy of Einstein's general theory of relativity: supermassive black holes. Connected to the evolution of the galaxies that contain these black holes, galactic nuclei are the sites of uniquely energetic events, including quasars, stellar tidal disruptions, and the generation of gravitational waves. This textbook is the first comprehensive introduction to dynamical processes occurring in the vicinity of supermassive black holes in their galactic environment. Filling a critical gap, it is an authoritative resource fo.